Estudo dos efeitos biológicos de uma desintegrina recombinante do veneno da serpente Bothrops alternatus, DisBa-01, sobre a musculatura da parede abdominal após indução de hérnia incisional em ratos - Oliveira, Claudio Ricardo de (Universidade Federal de São Carlos, 2009)
INTRODUCTION: The incisional hernia (IH) is one of the most frequent complications after laparotomy, causing high rates of re-operations. Advances in suture material, in the guidelines for incisions, in the techniques of closure and use of dentures (screens), have failed in the elimination of this surgical complication. In this context, advances in the understanding of biological and structural changes of collagen may offer a new strategy in the treatment of IH, since the matrix disorders that induces the formation of primary hernia probably also affect the wound healing in laparotomies. OBJECTIVE: To investigate the effect of a recombinant desintegrin (DisBa-01) on the abdominal muscle healing process with incisional hernia (IH) regarding the fibroblasts and vessels proliferation and matrix metalopeptidase activity as well. The role of α2 and anti- αvβ3 integrins were investigated by antibody competition. METHODS: IH was induced by sectioning of the midline in 20 Wistar rats, divided into two groups: control that received the topical application of phosphate buffered saline (PBS) and DisBa-01 protein (0.5mg/Kg) dissolved in PBS. Another 10 rats were divided in two groups: one received anti-αVβ3 antibodies and the second anti-α2 subunit antibodies. At the end of 14 days, the animals were sacrificed and muscle fragments were stored in liquid nitrogen for determination of MMPs by zymography. The remaining fragments of the control and DisBa-01 groups were fixed in 10% formol in PBS (v/v). Blood vessels density, mononuclear cells, fibroblasts and collagen fibers were studied by optical microscopy in blue reticuline and Masson-trichrome. Data was analyzed by parametric tests were applied with critical level of 5%. RESULTS: All animals after surgical induction developed IH. However, after 14 days the persistence of the opened hernial ring in the controls but not in the DisBa-01 group. This protein induced the formation of a membrane that occluded the entire hernial ring. A significant increase in the number of mononuclear cells, fibroblasts, new vessels and MMP-2 activity was observed in DisBa-01 group (p<0.05). DisBa-01 group significant increased the collagen content. Anti-αVβ3 integrin antibodies produced similar results but not anti-α2 integrin blocking antibodies. CONCLUSION: These results indicate that DisBa-01 promoted vascular and fibroblastic cell proliferation and monocytic, and matrix remodeling. In addition, these results strongly indicate that αVβ3 integrin has an important role in the control of would healing and the blocking of this integrin may be an interesting therapeutical strategy in tissue repair conditions, including IH.
Keywords: Hérnia ventral; Abdomen; DisBa-01; Cicatrização de feridas; Ratos; Ventral hernial; Abdomen; DisBa-01; Wound healing; Rats; CIENCIAS BIOLOGICAS::FISIOLOGIA